2017
DOI: 10.1002/jcop.21905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trauma exposure and acculturative stress on internalizing symptoms for recently arrived migrant‐origin youth: Results from a community‐based partnership

Abstract: Migrant youth face cultural challenges upon initial adjustment into the United States. Although there is considerable empirical evidence that trauma impacts interpersonal relations, there is a dearth of research examining the association between adverse events and the initial social and cultural exchange experience, and whether this is associated with psychological adjustment. This study examined self‐report data for 87 newly arrived migrant‐origin students in Grades 5–10 from Latin American, Caribbean, Asian,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Aunque sin duda los factores psicosociales y la resiliencia de los jóvenes migrados tiene un impacto profundo en su salud mental, la escuela es uno de los contextos comunitarios que más importancia tiene para la infancia y la adolescencia (Thibeault et al, 2017). Venta et al (2019) concluyeron en una investigación reciente que fomentar el compromiso escolar, un concepto fuertemente relacionado con la satisfacción escolar (Baker et al, 2003) y con la pertenencia a la escuela (Singh et al, 2010;Wang y Eccles, 2012), tenía una función protectora en la población migrada incluso mayor que el resto de los factores protectores clásicos, como la familia y los compañeros.…”
Section: Resiliencia Y Contexto Escolarunclassified
“…Aunque sin duda los factores psicosociales y la resiliencia de los jóvenes migrados tiene un impacto profundo en su salud mental, la escuela es uno de los contextos comunitarios que más importancia tiene para la infancia y la adolescencia (Thibeault et al, 2017). Venta et al (2019) concluyeron en una investigación reciente que fomentar el compromiso escolar, un concepto fuertemente relacionado con la satisfacción escolar (Baker et al, 2003) y con la pertenencia a la escuela (Singh et al, 2010;Wang y Eccles, 2012), tenía una función protectora en la población migrada incluso mayor que el resto de los factores protectores clásicos, como la familia y los compañeros.…”
Section: Resiliencia Y Contexto Escolarunclassified
“…Lastly, many Latino children are growing up in households with immigrant parents and/or grandparents. Immigrant children and adults experience risk due to challenges or trauma experienced prior to, during and post-migration to the USA (Thibeault, Mendez, Nelson-Gray, & Stein, 2017 ; Van Hook & Glick, 2020 ). Estimates based on the US Census data show 1 in 4 Latino children has a parent who lacks authorization to reside permanently in the USA (Clarke, Turner & Guzman, 2017 ).…”
Section: Characteristics Of Low-income Latino Childrenmentioning
confidence: 99%
“…In addition to rates of poverty, work has shown the high rates of exposure to traumatic events and acculturative stress among recently arriving immigrant children (Thibeault et al, 2017). Other unpredictable stressors facing Latinos include economic uncertainty (Vesely, et al, 2015), immigration policy and harmful impacts on families (Yoshikawa, et al, 2013), and uncertainty regarding eligibility for services (Alvira-Hammond & Gennetian, 2015).…”
Section: Overview Of Adversity and Resilience In Latino Childrenmentioning
confidence: 99%
“…The results of the above study were supported by a research conducted by Iverson et al (2011) who suggested that trauma is one of the general consequences that occurs in dating violence victims. Traumatic events are events that can also influence the occurrences of emotional disturbances, thinking and behavior, as well as disrupting one's ability to build and maintain interpersonal relationships, social skills, that can result in social isolation [35], [36]. Based on the results of the above research, it can be concluded that Post-Traumatic Stress Disorder is a direct impact for dating violence victims, and it will have a detrimental impact if no intervention is given to the victims.…”
Section: Pattern Of Traumatic Experience Of Intimate Partner Violencementioning
confidence: 99%